Effects of natural and synthetic antioxidant on the quality of beef in short-term preservation - Shohiduzjaman, M; Biplob, MAKA; Hashem, MA; Rahman, MM (Meat Research, 2024)
The experiment aimed to assess the effects of different natural and synthetic antioxidants and antimicrobial agents on the quality and shelf-life of fresh and preserved beef. Four treatment groups were used: T0 (control, no antioxidant), T1 (1% lemon peel extract), T2 (1% orange peel extract), and T3 (0.01% Butylated Hydroxytoluene, BHT). Beef samples were stored at 4°C for 9 days, and various tests were conducted on color, proximate components, physicochemical properties, biochemical markers, and microbial growth. Results showed that antioxidants significantly impacted physicochemical properties, oxidative defense, microbial growth, and sensory attributes, compared to the control. However, no significant changes were found in proximate components (CP, Ash, DM, EE). Antioxidant-treated samples showed lower pH levels but had no significant effect on water holding capacity. BHT (T3 ) exhibited the best results for oxidative stability, with lower TBARS values and reduced microbial counts. The sensory qualities, especially color, were improved in the lemon peel extract group (T1 ). Overall, BHT (T3 ) proved to be the most effective treatment for preserving beef quality, and it can be used up to 9 days for refrigeration-based preservation.